Anteseden Minat Beli Online di Marketplace Sociolla - Haning Kusuma; M. Trihudiyatmanto (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2021)
This study aims to determine the factors that influence online buying interest in the Sociolla marketplace. The variables studied were trust, ease of use, electronic word of mouth, and sales promotion. The background of this research is the decline in buying interest on the Sociolla website from July 2019 - September 2020. This study uses primary data generated from questionnaires. By using purposive sampling technique, obtained a sample of 108 respondents. The data analysis technique used the Structural Equation Model (SEM) with the help of AMOS software. The results of this study indicate that the variables of trust, use, electronic word of mouth, and sales promotion have a positive effect on online buying interest